Digital branding for Curug Luhur: Empowering community-based tourism through social media and content creation - Effendi, Harris; Nurhaida, Dida; Rezandi, Fajar; Winoto, Andre; Wardani, Ardila Puspita Kusuma (Community Empowerment, 2025)
Digital literacy gaps among rural tourism managers often hinder the promotion of local potential. This community service program aims to enhance the digital promotion capacity of Curug Luhur natural tourism managers in Sukabumi through social media management and content creation training. The approach integrates digital storytelling and digital branding strategies based on local wisdom. Implementation methods included smartphone-based photography/videography workshops and intensive mentoring on digital business account management. Evaluation results showed significant improvements: consistency in promotional content posts increased by 65%, technical skills in account creation rose by 60%, and understanding of digital performance analytics grew by 55%. Beyond technical aspects, the program successfully fostered a sense of belonging among participants, who now actively serve as community-based content creators and tourism ambassadors. This initiative demonstrates that digital literacy empowerment is an effective catalyst for strengthening the image of sustainable tourism destinations at the local level.